COMPLEX PERFORMANCE ANALYSIS OF MEDICAL INSTRUMENT ULTRASONIC MACHINING - Irina K. TSYBRIY; Elena V. VYAKHIREVA; Irina S. KUKHARENKO (Advanced Engineering Research)
Research results of the ultrasonic surface decontamination of the medical instrument in the complex with the structural material transformations occurring under the influence of ultrasonic vibrations are presented. The research work is aimed at the effective ultrasonic machinery modes selection.